Quality Development of a New Type Pharmaceutical Formulation - Erdei, Szabolcs; Budai, István (International Journal of Engineering and Management Sciences, 2022)
The aims of companies to understand internal and external customer demands in order to improve their existing products and develop new ones. Product development aims at understanding customer demands that may influence the production of the product to be manufactured. As a first step in the process, the customer voice method was used to define demands with measurable parameters. A questionnaire survey was used to prioritise them, which were then compared and ranked using a preference matrix. Within the QFD method, technical parameters influencing the satisfaction of customer demands were determined. A correlation matrix was established and the relationship between the technical parameters was investigated. A competition analysis of technical parameters and customer demands was carried out. From the absolute and relative weights, it is easy to establish the order of the technical parameters, so that the most important parameter in terms of meeting the defined customer demands is the determination of the ratio of raw materials, and important parameters are chemical stability, pharmaceutical formulation and particle size.